2020
DOI: 10.1002/elps.202000255
|View full text |Cite
|
Sign up to set email alerts
|

Protein dielectrophoresis: Key dielectric parameters and evolving theory

Abstract: Globular proteins exhibit dielectrophoresis (DEP) responses in experiments where the applied field gradient factor ∇E2 appears far too small, according to standard DEP theory, to overcome dispersive forces associated with the thermal energy kT of disorder. To address this a DEP force equation is proposed that replaces a previous empirical relationship between the macroscopic and microscopic forms of the Clausius–Mossotti factor. This equation relates the DEP response of a protein directly to the dielectric inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 80 publications
(172 reference statements)
3
40
0
Order By: Relevance
“…This empirical-based suggestion mirrors various theoretical findings of Matyushov and co-workers [8,10]. The possible significance of this for further development of a robust theory for protein DEP is discussed in an accompanying paper [11].…”
Section: Concluding Commentssupporting
confidence: 80%
See 2 more Smart Citations
“…This empirical-based suggestion mirrors various theoretical findings of Matyushov and co-workers [8,10]. The possible significance of this for further development of a robust theory for protein DEP is discussed in an accompanying paper [11].…”
Section: Concluding Commentssupporting
confidence: 80%
“…The purpose of this and an accompanying paper [11] is to critically evaluate the protein DEP literature, to derive an empirical-based theory, and to then describe and summarize the molecular-based theory developed by Matyushov and colleagues [8,10]. In this paper we examine aspects of the reported protein DEP work not covered in previous reviews, and conclude that the reported DEP responses for a range of proteins are largely consistent.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…There is an ongoing evolution of the theoretical underpinnings of electric field gradient techniques, where past physical descriptors were limited to conductivity and permittivity of the particle. 20 It is becoming better understood that the overall structure and subtle details of the bioparticle, including the particle-solvent cross polarizations, will influence these forces [20][21][22]55,56 . This new view of the forces imparted on the insulin vesicles aligns with a rather simple proposition that the makeup of the particle has changed: something has been added, subtracted, or altered which changed the force on the particle in a measurable and quantifiable way.…”
Section: Discussionmentioning
confidence: 99%
“…For the Lorentz cavity field employed in the derivation of [CM] molecular , there is a maximum cavity size above which cavity field theory breaks down. This interesting situation [24] could provide an experimental approach to determining and controlling a threshold for the particle size above which protein DEP is governed by [CM] macro rather than [CM] molecular . For example, in an assessment of future protein-based drug carriers, standard DEP theory correctly predicts the reported separation by negative DEP of micron-sized designer protein particles according to their size and shape [25].…”
Section: Introductionmentioning
confidence: 99%